1990
DOI: 10.1038/bjc.1990.261
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer and lymphokine activated killer cell functions in Hodgkin's disease

Abstract: Summary We report the natural killer (NK) and lymphokine activated killer (LAK) cell activities in peripheral blood lymphocytes (PBL) from untreated patients with Hodgkin's disease (HD) and from healthy donors. The frequency of LAK cell precursors was also studied using limiting dilution analysis (LDA). About 75% of the HD patients had normal NK activity. There was a higher percentage of low NK responders (mean percent NK activity of healthy donors -2 SD) in patients with lymphocyte depletion histologic grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
0
5
1
Order By: Relevance
“…Some earlier studies, focusing on enumeration of NK cells, indicated a decrease in their number in active states of HD (Berenyi et al , 1996). Unlike our and previous findings, Rajaram et al (1990) reported normal NK‐cell activity for patients with active HD, except for those with histological type of lymphocyte depletion and clinical stage IV. Nevertheless, the found impairment in NK‐cell function is supported by the findings of alterations of NK‐cell subsets in HD patients (Macklis et al , 1993) and reported increased serum CD8 soluble antigen levels indicative of suppressive T‐cell function (Grinfors et al , 1992).…”
Section: Discussioncontrasting
confidence: 99%
“…Some earlier studies, focusing on enumeration of NK cells, indicated a decrease in their number in active states of HD (Berenyi et al , 1996). Unlike our and previous findings, Rajaram et al (1990) reported normal NK‐cell activity for patients with active HD, except for those with histological type of lymphocyte depletion and clinical stage IV. Nevertheless, the found impairment in NK‐cell function is supported by the findings of alterations of NK‐cell subsets in HD patients (Macklis et al , 1993) and reported increased serum CD8 soluble antigen levels indicative of suppressive T‐cell function (Grinfors et al , 1992).…”
Section: Discussioncontrasting
confidence: 99%
“…In untreated patients with Hodgkin's disease differing levels of NK cytotoxicity have been reported (Al Sam et al 1982;Gupta & Fernandes 1982;Frydecka et al 1985;Rajaram et al 1990). Our results showed an increase in NK cell activity in untreated patients compared with controls, in accordance with the results of Al Sam et al (1982) activity of the 11 patients studied before and after treatment was significantly increased after treatment (P = 0.016).…”
Section: Discussionmentioning
confidence: 99%
“…A number of immunological defects have been described during the course of Hodgkin's disease (HD) and as a result of its treatment. Some studies have shown normal NK cell activity pretreatment (Gupta & Fernandes 1982;Rajaram et al 1990), others have reported a reduced activity in untreated patients and in patients in the active phase of the disease during treatment (Frydecka 1985), while others have reported an increase in NK activity in the spleen of untreated patients (Al Sam et al 1982) and in the peripheral blood of HD patients following treatment (Macklis et al 1992;Macklis et al 1993). Lymphoid irradiation results in long-term increases in the number of NK cells (Macklis et al 1992) which appears to be a generalized expansion of the entire NK cell compartment rather than an increase in any specific NK cell subset (Macklis et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore it could be envisaged that LAK cells would also contribute to sIL-2R by shedding the receptors in which case their effector function would be jeopardized. However, we have found that in HD, the NK and LAK activities of the PBL were within the normal range or higher (Rajaram et al, 1990). In order to correlate high levels of sIL-2R with NK/LAK activity in HD, assessment of the 3 parameters need to be performed in the same patients.…”
Section: Lymphocytes From Healthy Donorsmentioning
confidence: 92%